Surgical complications occurring during minimally invasive sentinel lymph node detection in endometrial cancer patients. A systematic review of the literature and metanalysis. Issue 8 (August 2021) - Capozzi, Vito Andrea; Riemma, Gaetano; Rosati, Andrea; Vargiu, Virginia; Granese, Roberta; Ercoli, Alfredo; Cianci, Stefano
Abstract: Introduction: Endometrial cancer (EC) is the most common gynecological cancer. Sentinel lymph node (SLN) technique has been adopted worldwide and showed lower morbidity and superimposable survival outcomes than the systematic lymphadenectomy (LND). Although these encouraging results, no meta-analyzes were performed on surgical complications during SLN research among patients undergoing laparoscopic (L) versus robotic surgery (R). The present review aims to report surgical complications during laparoscopic versus robotic SLN technique. Methods: The Preferred Reporting Items for Systematic reviews and Meta-Analyzes (PRISMA) and the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines have been followed for the present meta-analysis. Results: Six studies, including 769 participants, were included. L-LND resulted in a significantly higher risk of operative complications relative to L-SLN (RR 2.10 [95% CI 1.37 to 3.21]). The risk of complications was comparable between R-SLN and L-SLN (RR 2.32 [95% CI 0.04–121.02]) and between R-LND and L-LND (RR 2.17 [95% CI 0.04–126.69]). According to the SUCRA analysis, L-SLN and R-SLN had the highest chances of being ranked first among proposed surgical procedures (SUCRA 48.9% and 28.4% respectively). Conclusions: Our study reported a lower surgical complications rate in patients undergoing L-SLN technique compared to L-LND. A lower rate of surgical complications was also reported for the R-SLN technique compared to the R-LND. Both laparoscopic and robotic SLN surgical techniques were found to be safe surgical procedures.